2013
DOI: 10.1177/1464420713485536
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbon fibres for reinforcement of thin geopolymer cement sections

Abstract: An alkali-activated aluminosilicate geopolymer cement was reinforced with polyether ether ketone-wound carbon fibre layers to improve the mechanical properties of the cement in flexion. Such a material, which is heat resistant and has a low coefficient of thermal expansion, will be of use in the development of out-of-autoclave processing routes for large area composite components. The mechanical and physicochemical properties of both the neat and reinforced cement were examined using Charpy impact and three-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The mechanical and physicochemical properties of both neat and reinforced cement were tested using the Charpy impact test and three-point bending test. A five-fold increase in flexural strength was observed for fiber-reinforced geopolymer specimens and a three-fold increase in impact strength was observed as well [58]. As a result of the study, it was observed that the best compressive strength results for specimens with the addition of carbon fibers were obtained for geopolymer-cement hybrids with 0.5% fiber addition with a length of 5 mm.…”
Section: Carbon Fiber Reinforcement Of Geopolymersmentioning
confidence: 64%
See 2 more Smart Citations
“…The mechanical and physicochemical properties of both neat and reinforced cement were tested using the Charpy impact test and three-point bending test. A five-fold increase in flexural strength was observed for fiber-reinforced geopolymer specimens and a three-fold increase in impact strength was observed as well [58]. As a result of the study, it was observed that the best compressive strength results for specimens with the addition of carbon fibers were obtained for geopolymer-cement hybrids with 0.5% fiber addition with a length of 5 mm.…”
Section: Carbon Fiber Reinforcement Of Geopolymersmentioning
confidence: 64%
“…The mechanical and physicochemical properties of both neat and reinforced cement were tested using the Charpy impact test and three-point bending test. A five-fold increase in flexural strength was observed for fiber-reinforced geopolymer specimens and a three-fold increase in impact strength was observed as well [58].…”
Section: Reinforcement Of Geopolymers With Basalt Gridmentioning
confidence: 85%
See 1 more Smart Citation